COWPEA [VIGNA UNGUICULATA (L.) WALP.] CROPPING SYSTEMS MAPPING AND FARMERS’ PERCEPTION ON SOIL FERTILITY IN BENIN(1) - Anago, Firmin N; DAGBENONBAKIN, Gustave D.; AGBANGBA, Codjo Emile; Oussou, Brice; CHABI, Faki; SAIDOU, ALIOU; AMADJI, LUCIEN GUILLAUME (My University, 2020)
Cowpea is an important legume crop in West Africa. However, in Benin, the cowpea grain yield is very low due to the soil depletion which induces food insecurity. To better understand the current management of soil fertility under cowpea production and farmers’ perception on soil fertility, survey was conducted among 562 farmers in three geographical zones (southern, central and northern) of Benin. Results showed that main areas under cowpea production are in central (1.09 ± 0.85 ha) and southern (1.28 ± 1.16 ha) Benin. Three cowpea cropping systems were identified. There are farmers (13.18%) who grow cowpea in association with a cereal, use mineral fertilizers, practice manual tillage and bury crop residues in the soil. This practice is more observed in southern Benin where there was a low availability of arable land. The second cropping system involves farmers (56.22 %) who grow cowpea in a rotation system without intercropping and mineral fertilizer but practice manual tillage and bury crop residues on the soil. This system was more adopted in central Benin. The third crop system was observed in the northern part of the country where farmers (30.60 %) grow pure cowpea in a rotation system with a harnessed tillage and crop residues were used as animal feed. Farmers in all areas recognized that soil fertility was declining, based primarily on changes in yields. This decline in soil fertility is the main abiotic constraint that limits the production of cowpea. Then, determination of fertilizer rates which optimize cowpea yield is necessary to improve its productivity.
Keywords: endogenous knowledge; declining of soil fertility; rotation system